Empathy in the Quran Perspective and its Actualization on Humanitarian Issues in Palestine - Hidayati, Nur; Musafaah, Suqiyah; Pratiwi, Rohmania Citra Ayu; Fadzil, Huda (Universitas Muhammadiyah Surakarta, 2025)
The research aims to study about the concept of empathy in the Qurann and the relevant and actuality on Palestine of humanity issue. The Research used qualitative methods with thematic tafsir. Focus on Collective data and analysis phrases from the Quran that are relevant with empathy. The conclusion of this research shows That empathy the Quran was explained from the norm of rahmah (love), 'adl (justice), ihsan (kindness), and sadaqah (giving). The norm of empathy is not only to have emotional feeling, but also to teach the implementation of empati in the trim of solidarity. Human avocation and boikot products support penjajah. Fungsi riset identified several challenges on equalization of empati in the modern era such as individualisme, empathy in social media and geopolitik. Spesifik contribution from the research to enhance understanding the theme of empathy in the al-quran same as context and can become application in the real Era as Foundation Of Islamic people to contribute on the Human issue. Further research should increase the understanding of implementation empati in the Quran with the policy of Education and other differences of culture.